Lab Attendance and Academic Performance. (9th May 2012) - Adair, Kirk; Swinton, Omari H.
Abstract : The benefits from attendance of lectures have been established in the literature. This paper focuses on attendance not of the lecture, but of smaller labs. These labs are 50 minutes one-day-a-week sessions to emphasis material covered during lecture. Using a 200-student Principles of Economics class that covers microeconomics with six different labs, we investigate the effect of lab attendance on exam performance by taking into account individual characteristics. We find that lab attendance benefits the student in overall exam performance.